RANCANG BANGUN ALAT PEMBERI PAKAN DAN PENGGANTI AIR AQUARIUM OTOMATIS BERBASIS ARDUINO UNO: Array (JiTEKH, 2019)
Along the development nowadays it is really needed for automatic aquariums which really helps us in doing the water replacement and feeders for fish, which the time usually will be set up on it to replace water and feeders and it will waste time especially in any busy conditions, therefore it was designed a device called Arduino-based automatical fish feeder and water replacement for aquarium. This device used Arduino as a controller device to drive the whole system. This device used a turbidity sensor that served to detect muddy water in the aquarium. Water level sensor was used for measuring water levels in aquarium. The servo motor would give an order to Arduino to open the feeder for fish. Relay was used to turn off and turn on the water pump in aquarium, where first water pump and second water pump also functioned for water disposal and replacement. The buzzer also was used to provide sound signals for feeders and water replacement. LCD would be functioned to display the time, date, woof, and water replacement warning, while Rtc was used to save the time and date.